Phenotype-Based HPLC-Q-TOF-MS/MS Coupled With Zebrafish Behavior Trajectory Analysis System for the Identification of the Antidepressant Components in Methanol Extract of Anshen Buxin Six Pills - Jiani Liu (Frontiers Media S.A., 2021)
Phenotype screening has become an important tool for the discovery of active components in traditional Chinese medicine. Anshen Buxin Six Pills (ASBX) are a traditional Mongolian medicine used for the treatment of neurosis in clinical settings. However, its antidepressant components have not been explicitly identified and studied. Here, the antidepressant effect of ASBX was evaluated in adult zebrafish. High performance liquid chromatography-mass spectrometry (HPLC-Q-TOF-MS/MS) was combined with zebrafish behavior trajectory analysis to screen and identify the antidepressant-active extract fraction and active components of ASBX. Finally, the antidepressant effect of the active ingredients were verified by the behavior, pathology, biochemical indices and protein level of adult fish. The novel tank driving test (NTDT) showed that ASBX can effectively improve the depressive effect of reserpine on zebrafish. Petroleum ether and dichloromethane extracts of ASBX were screened as antidepressant active extracts. Costunolide (COS) and dehydrocostus lactone (DHE) were screened as the active components of ASBX. COS had been shown to significantly improve the depressive behavior, nerve injury and neurotransmitter levels (5-hydroxytryptamine (5-HT) and norepinephrine (NE)) of zebrafish by inhibiting the high expression of serotonin transporter and norepinephrine transporter induced by reserpine suggesting the antidepressant effect of COS may be related to its effect on 5-HT and NE pathways. This study provided a phenotype based screening method for antidepressant components of traditional Chinese medicines, so as to realize the separation, identification and activity screening of components at the same time.